Slurry composition, cured product of said slurry composition, and substrate, film, and prepreg using said cured product

The slurry composition with a cyclic imide compound and spherical particles addresses filler aggregation and handling issues, providing a cured product with excellent mechanical and dielectric properties for high-frequency applications.

JP7607398B2Active Publication Date: 2024-12-27SHIN ETSU CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2019072411
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-04-05
Publication Date
2024-12-27
Estimated Expiration
2039-04-05

AI Technical Summary

Technical Problem

Existing methods for dispersing fillers in matrix resins for printed wiring boards face challenges with filler aggregation and poor handling properties, leading to difficulties in producing thin films with high-frequency compatibility.

Method used

A slurry composition comprising a cyclic imide compound, spherical silica or alumina particles, a silane coupling agent, and an organic solvent, with a thixotropic ratio of 3.0 or less, ensuring excellent handling and dielectric properties.

Benefits of technology

The composition achieves low thixotropy, enabling easy film formation and results in a cured product with superior mechanical strength and dielectric properties, suitable for high-frequency equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607398000001
    Figure 0007607398000001
  • Figure 0007607398000002
    Figure 0007607398000002
  • Figure 0007607398000003
    Figure 0007607398000003
Patent Text Reader

Abstract

To provide a slurry composition having low thixotropy and excellent handleability, a cured product of the slurry composition, and a substrate, a film, and a prepreg which use the cured product and have excellent mechanical characteristics, a low dielectric constant and a low dielectric loss tangent.SOLUTION: The slurry composition contains the following components (A)-(D) and has a thixotropic ratio of 3.0 or less: (A) a cyclic imide compound containing at least one dimer acid skeleton, at least one C6 or higher linear alkylene group, and at least two cyclic imide groups in the molecule; (B) spherical silica fine particles and / or alumina fine particles having an average particle diameter of 0.05-20 μm as measured by a laser diffraction method; (C) a silane coupling agent capable of reacting with the component (A) and the component (B); and (D) an organic solvent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a slurry composition, a cured product of the slurry composition, and a substrate, a film, and a prepreg using the cured product. [Background technology]

[0002] A method for producing a resin molded product such as a sheet or film by coating a resin dissolved in an organic solvent is commonly used. In order to improve the mechanical strength, heat resistance, non-absorption, and other properties of the resin molded product, a filler of oxide particles is often dispersed in the matrix resin to achieve high loading.

[0003] In the past, when dispersing the filler in a matrix resin to achieve high loading, the mainstream method was to directly add the filler to a matrix resin dissolved in an organic solvent, and then knead and disperse the resulting mixture using a kneader or disperser such as a gate mixer or a three-roll mill. However, this method had problems in that when the filler particles were small, it was difficult to disperse the filler in the matrix resin, and aggregates of the filler particles were formed in the matrix resin, and the quality of the matrix resin in which the filler was dispersed was prone to vary.

[0004] On the other hand, in mobile communication devices such as mobile phones, their base station equipment, servers, and network infrastructure devices such as routers, and electronic devices such as large computers, the speed and capacity of the signals used are increasing year by year. Accordingly, the printed wiring boards mounted on these electronic devices must be compatible with high frequencies such as the 20 GHz range, and substrate materials with low relative dielectric constants and low dielectric loss tangents that enable reduction in transmission loss are required. In recent years, in addition to the above-mentioned electronic devices, new systems that handle high-frequency signals in the fields of intelligent road transport systems and indoor short-distance communication have been put into practical use and are planned to be put into practical use as applications that handle such high-frequency signals, and it is expected that in the future, low transmission loss substrate materials will be further required for the printed wiring boards mounted on these devices.

[0005] Conventionally, polyphenylene ether (PPE) resins have been used as heat-resistant thermoplastic polymers that exhibit low dielectric constants and low dielectric loss tangents even in high frequency regions for printed wiring boards that require low transmission loss. As a method for using polyphenylene ether resins, a method of using polyphenylene ether in combination with a thermosetting resin has been proposed (Patent Documents 1 and 2). Fluorinated resins are also known as materials that exhibit low dielectric constants and low dielectric loss tangents and are used, but have the disadvantage of being poor in processability.

[0006] Furthermore, the use of maleimide compounds as materials for printed wiring boards has also been considered. For example, a resin composition is known that contains a maleimide compound having at least two maleimide skeletons, an aromatic diamine compound having at least two amino groups and an aromatic ring structure, a catalyst having a basic group and a phenolic hydroxyl group that promotes the reaction between the maleimide compound and the aromatic diamine compound, and silica (Patent Document 3). Also known is a resin composition that contains a long-chain alkyl bismaleimide resin having a main chain containing an alkylene chain having 10 or more carbon atoms and a side chain containing an alkyl group bonded to the alkylene chain, and a curing agent having two or more functional groups that react with the long-chain alkyl bismaleimide resin (Patent Document 4).

[0007] Based on these circumstances, a method of mixing a compound having a maleimide group with an inorganic filler slurry is known as a method of manufacturing a resin film for manufacturing a printed wiring board for a millimeter wave radar (Patent Document 5). However, in this method, the mixture of the compound having a maleimide group and the inorganic filler slurry tends to have poor handleability, for example, due to high thixotropy. For example, if appropriate materials or surface treatments are not selected, the thixotropy will be high, and when producing a thin film, etc., high shear stress will be applied to the narrow gap between the blade and the release film, making thin film coating difficult. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2010-059363 A [Patent Document 2] JP 2010-275342 A [Patent Document 3] JP 2012-255059 A [Patent Document 4] Re-tabled publication No. 2016-114287 [Patent Document 5] JP 2017-125128 A Summary of the Invention [Problem to be solved by the invention]

[0009] Accordingly, an object of the present invention is to provide a slurry composition having low thixotropy and excellent handleability, a cured product of the slurry composition, and a substrate, film, and prepreg using the cured product, which have excellent mechanical properties and a low dielectric constant and dielectric tangent. [Means for solving the problem]

[0010] Means of the Invention The present inventors have conducted extensive research to solve the above problems and have found that the following slurry composition can achieve the above object, thereby completing the present invention.

[0011] <1> A slurry composition comprising the following components (A) to (D) and having a thixotropic ratio of 3.0 or less: (A) A cyclic imide compound containing at least one dimer acid skeleton, at least one linear alkylene group having 6 or more carbon atoms, and at least two cyclic imide groups in the molecule. (B) Spherical silica fine particles and / or alumina fine particles having an average particle size of 0.05 to 20 μm as measured by a laser diffraction method (C) A silane coupling agent capable of reacting with components (A) and (B). (D) Organic solvent <2> The cyclic imide compound of the component (A) is represented by the following formula (1): <1> The slurry composition according to claim 1. [ka] (In formula (1), A independently represents a tetravalent organic group containing an aromatic ring or an aliphatic ring. B independently represents an alkylene chain having 6 to 18 carbon atoms and having an aliphatic ring which may contain a divalent heteroatom. Q independently represents a linear alkylene group having 6 or more carbon atoms. R independently represents a linear or branched alkyl group having 6 or more carbon atoms. n independently represents a number from 1 to 10. m independently represents a number from 0 to 10.) <3> In the formula (1), A is any one of the following structures: <2> The slurry composition according to claim 1. [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).) <4> The ratio of the fine particles of the component (B) is 30% by mass or more and 95% by mass or less of the entire slurry composition. <1> from <3> 2. The slurry composition according to claim 1 . <5> The silane coupling agent, which is the component (C), has a (meth)acrylic group and / or an amino group. <1> from <4> 2. The slurry composition according to claim 1 . <6> A cured product of the slurry composition according to any one of claims 1 to 5. <7> It is a substrate <6> The cured product according to claim 1. <8> It is a film <6> The cured product according to claim 1. <9> It is a prepreg <6> The cured product according to claim 1. <10> The following components (A) to (D) (A) A cyclic imide compound containing at least one dimer acid skeleton, at least one linear alkylene group having 6 or more carbon atoms, and at least two cyclic imide groups in the molecule. (B) Spherical silica fine particles and / or alumina fine particles having an average particle size of 0.05 to 20 μm as measured by a laser diffraction method (C) a silane coupling agent capable of reacting with components (A) and (B), and (D) Organic solvent 5. A method for producing a slurry composition, comprising the step of mixing the above components, wherein the method for producing component (B) is a VMC (Vaporized Metal Combution) method. Effect of the Invention

[0012] The slurry composition of the present invention has low thixotropy and is easy to handle when it is made into a film, etc. Furthermore, when this composition is cured, the cured product has excellent physical strength and dielectric properties, and therefore, substrates, films, prepregs, etc. having the cured product are suitable as materials for high-frequency devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will now be described in more detail.

[0014] (A) Cyclic imide compound Component (A) is a cyclic imide compound of a thermosetting resin component, and has at least one dimer acid skeleton, at least one linear alkylene group having 6 or more carbon atoms, and at least two cyclic imide groups in the molecule. Since the cyclic imide compound of component (A) has a linear alkylene group having 6 or more carbon atoms, the cured product of the composition containing it not only has excellent dielectric properties, but also has a reduced phenyl group content and improved tracking resistance. Furthermore, since the cyclic imide compound of component (A) has a linear alkylene group, the cured product of the composition containing it can have low elasticity.

[0015] The cyclic imide compound of the component (A) is preferably a maleimide compound, and it is more preferable to use a maleimide compound represented by the following formula (1). [ka] In formula (1), A independently represents a tetravalent organic group containing an aromatic ring or an aliphatic ring. B independently represents an alkylene group having 6 to 18 carbon atoms and having an aliphatic ring which may contain a divalent heteroatom. Q independently represents a linear alkylene group having 6 or more carbon atoms. R independently represents a linear or branched alkyl group having 6 or more carbon atoms. n independently represents a number from 1 to 10. m independently represents a number from 0 to 10.

[0016] Q in formula (1) is a linear alkylene group having 6 or more carbon atoms, preferably 6 or more and 20 or less, and more preferably 7 or more and 15 or less.

[0017] Furthermore, R in formula (1) is an alkyl group, which may be a straight-chain or branched alkyl group, and has 6 or more carbon atoms, preferably 6 or more and 12 or less carbon atoms.

[0018] In formula (1), A represents a tetravalent organic group containing an aromatic ring or an aliphatic ring, and is particularly preferably any of the tetravalent organic groups represented by the following structural formulas. [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).)

[0019] Furthermore, B in formula (1) is an alkylene group having 6 to 18 carbon atoms and an aliphatic ring which may contain a divalent heteroatom, and the number of carbon atoms in the alkylene group is preferably 8 to 15. B in formula (1) is preferably any of the alkylene groups having an aliphatic ring represented by the following structural formulas. [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom forming a cyclic imide structure in formula (1).)

[0020] In the formula (1), n ​​is a number from 1 to 10, and preferably a number from 2 to 7. In the formula (1), m is a number from 0 to 10, and preferably a number from 0 to 7.

[0021] The weight average molecular weight (Mw) of the cyclic imide compound of component (A) is not particularly limited, including its properties at room temperature, but the weight average molecular weight calculated using polystyrene standards by gel permeation chromatography (GPC) is more preferably 500 to 50,000, and particularly preferably 800 to 40,000. If the molecular weight is 500 or more, the resulting composition containing the cyclic imide compound is easily formed into a film, and if the molecular weight is 50,000 or less, the resulting composition does not have too high a viscosity and is not likely to reduce flowability, resulting in good moldability in lamination molding and the like.

[0022] As the cyclic imide compound of the component (A), commercially available products such as BMI-689, BMI-1500, BMI-2500, BMI-2560, BMI-3000, and BMI-5000 (all manufactured by Designer Molecules Inc.) can be used. The cyclic imide compound may be used alone or in combination of two or more types.

[0023] The composition of the present invention contains the component (A) in an amount of preferably 10 to 90 mass %, more preferably 15 to 85 mass %, and even more preferably 20 to 80 mass %.

[0024] (B) Spherical silica fine particles and / or alumina fine particles having an average particle size of 0.05 to 20 μm as measured by a laser diffraction method The slurry composition of the present invention contains silica fine particles and / or alumina fine particles as component (B). The silica fine particles and / or alumina fine particles are spherical particles having an average particle size of 0.05 to 20 μm measured by a laser diffraction method, and may be used alone or in combination. In the present invention, "spherical" refers to particles having a sphericity in the range of 0.8 to 1.0. The sphericity is the average value of the ratio of the minimum diameter / maximum diameter of each particle when 100 particles are randomly selected. There are no particular limitations on the shape, but a spherical shape is preferable from the viewpoint of packing properties, etc.

[0025] The silica fine particles and / or alumina fine particles used in the present invention must have an average particle size measured by a laser diffraction method of 0.05 to 20 μm, preferably 0.05 to 15 μm, and more preferably 0.1 to 10 μm. If the average particle size is less than 0.05 μm, the viscosity increases, which reduces moldability, and if the average particle size exceeds 20 μm, the flatness of molded products such as films decreases, which is also undesirable. The average particle size is the median diameter (D 50 ) value.

[0026] The method for producing the above-mentioned silica and alumina fine particles is not particularly limited, but they are preferably produced by the VMC (Vaporized Metal Combution) method. The VMC method is a method in which a chemical flame is formed by a burner in an oxygen-containing atmosphere, and a metal powder constituting a part of the target oxide fine particles is added to this chemical flame in an amount sufficient to form a dust cloud, causing a deflagration to produce oxide fine particles.

[0027] The operation of the VMC method can be explained as follows. First, a container is filled with a gas containing oxygen, which is a reactive gas, and a chemical flame is formed in this reactive gas. Next, metal powder is added to this chemical flame and a high concentration (500 g / m 3A dust cloud of 10 ...

[0028] The VMC method utilizes the principle of dust explosion, and can instantly produce large amounts of oxide fine particles, with extremely high sphericity. For example, silicon powder can be added to obtain silica fine particles, and aluminum powder can be added to obtain alumina fine particles. By adjusting the particle size of the powder added, the amount added, the flame temperature, etc., it is possible to adjust the particle size of the fine particles, and it is also possible to easily produce ultrafine particles with a particle size on the submicron order.

[0029] The ratio of the fine particles of the (B) component to the entire slurry composition is 30% by mass or more and 95% by mass or less, and preferably 35% by mass or more and 90% by mass or less. If the ratio is less than 30% by mass, not only are the fine particles likely to settle, but also repellency tends to occur during coating. If the ratio is more than 95% by mass, the viscosity tends to be too high, and the handling properties tend to decrease.

[0030] (C) A silane coupling agent capable of reacting with components (A) and (B). The slurry composition of the present invention uses, as component (C), a silane coupling agent capable of reacting with the cyclic imide compound (A) and the silica fine particles and / or alumina fine particles (B). Examples of such coupling agents include epoxy group-containing alkoxysilanes, amino group-containing alkoxysilanes, (meth)acrylic group-containing alkoxysilanes, and unsaturated alkyl group-containing alkoxysilanes.

[0031] Among them, (meth)acrylic and / or amino group-containing alkoxysilanes are preferably used from the viewpoint of reducing the viscosity and thixotropy of the slurry composition, improving the mechanical strength and dielectric properties of the cured product, and improving adhesion to metals such as copper.Specific examples of the (C) component include 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, and 3-aminopropyltrimethoxysilane.

[0032] The content of component (C) is preferably 0.1 to 8.0% by mass, particularly preferably 0.3 to 6.0% by mass, based on the total of thermosetting resin components including component (A). If the content is less than 0.1% by mass, the adhesive effect to the substrate and the wettability to silica fine particles and / or alumina fine particles are insufficient, while if the content exceeds 8.0% by mass, the viscosity is extremely reduced even after removing the organic solvent of component (D) described below, which may cause voids or bleeding from the resin surface.

[0033] (D) Organic solvent The slurry composition of the present invention contains an organic solvent as component (D). The type of organic solvent is not limited, but it is preferable that the organic solvent is a good solvent for the cyclic imide compound, which is component (A). As component (D), for example, aliphatic hydrocarbons such as hexane and heptane; aromatic hydrocarbons such as xylene and toluene; ketone compounds such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; alcohol compounds such as isopropanol (IPA) and n-butanol; ether compounds such as dibutyl ether and tetrahydrofuran (THF); sulfoxide compounds such as dimethyl sulfoxide (DMSO); amide compounds such as dimethylformamide (DMF) and N-methyl-2-pyrrolidone; and ester compounds such as ethyl acetate and propylene glycol monomethyl ether acetate (PGMEA) can be used. However, from the viewpoint of the solubility of component (A), it is preferable to use aromatic hydrocarbon organic solvents such as xylene and toluene.

[0034] The blend amount of component (D) is preferably 10 to 500 parts by mass, and particularly preferably 20 to 200 parts by mass, per 100 parts by mass of the total of components (A) and (B).

[0035] Other Additives The slurry composition of the present invention may further contain various additives as necessary. As the additives, within a range that does not impair the effects of the present invention, thermosetting resins such as epoxy resins, organopolysiloxanes, silicone oils, thermoplastic resins, thermoplastic elastomers, organic synthetic rubbers, light stabilizers, polymerization inhibitors, flame retardants, pigments, dyes, curing accelerators, catalysts, inorganic fillers other than silica fine particles and alumina fine particles, etc. may be added to improve resin properties, and ion trapping agents, etc. may be added to improve electrical properties. Furthermore, fluorine-containing materials, etc. may be added to improve dielectric properties.

[0036] Preparation of the Slurry Composition When producing the slurry composition of the present invention, the order of addition of each component and the method of dispersion are not particularly limited. For example, the cyclic imide compound (A), the fine powder of silica or alumina (B), which is an inorganic filler, and the silane coupling agent (C) may be dispersed in the organic solvent (D), or the component (A) may be dissolved in the component (D) to prepare a varnish, and the components (B) and (C) may be added thereto and then dispersed. Dispersion may be performed using equipment such as a three-roll mill, a ball mill, an ultrasonic disperser, various mixers, and a kneader. In order to prevent the denaturation of the slurry composition, it is preferable to produce the composition in a non-oxidizing atmosphere such as a nitrogen atmosphere.

[0037] The thixotropy ratio of the obtained slurry composition of the present invention is 3.0 or less. If the thixotropy ratio is greater than 3.0, the composition is likely to have poor handleability. For example, if appropriate materials or surface treatments are not selected, the thixotropy will be high, and when producing a thin film, etc., a high shear stress will be applied to the narrow gap between the blade and the release film, making thin film coating difficult.

[0038] The thixotropy ratio in this case was calculated using the viscosity values ​​obtained in measurements performed at 25°C / 5 rpm and 50 rpm using a cone-plate type rotational viscometer (E-type viscometer) described in JIS K 7117-2:1999. Thixotropy ratio = (viscosity measured at 5 rpm [Pa s]) / (viscosity measured at 50 rpm [Pa s]) In this case, the viscosity at 25° C. / 5 rpm is preferably in the range of 0.01 to 10 Pa.s, and the viscosity at 25° C. / 50 rpm is preferably in the range of 0.01 to 7.5 Pa.s.

[0039] The inorganic filler, which is component (B), may react with component (C), i.e., may be surface-treated with component (C). The method of surface treatment is not particularly limited, and may be performed according to a method generally used. For example, component (B) may be subjected to a dry treatment beforehand and then put into an organic solvent, or may be treated in an organic solvent as a wet treatment. In addition, component (B) may be added simultaneously with component (A), and the order of addition of each component is arbitrary.

[0040] The slurry composition of the present invention can be coated by a method such as spraying, roll coating, spin coating, casting, dipping, etc. after adding a curing accelerator (radical initiator) such as peroxide, and then cured after evaporating the solvent to form a molded product (substrate, film, prepreg, etc.). In this case, the molded product can be used for various applications such as electronic parts, adhesives, heat-resistant films, protective films, etc., and is suitable as a material for high-frequency devices. Here, the preferred conditions for the step of evaporating the solvent are a temperature range of 80 to 150°C for 0.5 to 4 hours, and the preferred conditions for the step of curing the slurry composition of the present invention are a temperature range of 150 to 200°C for 1 to 16 hours.

[0041] The above-mentioned embodiment of the slurry composition of the present invention is merely an example, and the slurry composition of the present invention is not limited to the above-mentioned embodiment. The slurry composition of the present invention can be implemented in various forms including the above-mentioned embodiment and various improvements and modifications that can be made by a person skilled in the art. EXAMPLES

[0042] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0043] (A) Cyclic imide compound (A-1): A straight-chain alkylene group-containing maleimide compound represented by the following formula (BMI-3000, manufactured by Designer Molecules Inc.) [ka] (A-2): A straight-chain alkylene group-containing maleimide compound represented by the following formula (BMI-2500, manufactured by Designer Molecules Inc.) [ka] (A-3) 4,4'-diphenylmethane bismaleimide (BMI-1000: manufactured by Daiwa Kasei Co., Ltd., for comparison)

[0044] (B) Spherical silica fine particles and / or alumina fine particles having an average particle size of 0.05 to 20 μm as measured by a laser diffraction method (B-1) Spherical silica (Admafine SO-C5, manufactured by Admatechs, produced by the VMC method, average particle size 1.5 μm) (B-2) Spherical alumina (Admafine AO-502, manufactured by Admatechs, produced by the VMC method, average particle size 0.7 μm) (B-3) Fused spherical silica (ES-105, manufactured by Tokai Minerals, average particle size 35 μm, for comparison)

[0045] (C) A silane coupling agent capable of reacting with components (A) and (B). (C-1) 3-Methacryloxypropyltrimethoxysilane (KBM-503, Shin-Etsu Chemical Co., Ltd.) (C-2) 3-Acryloxypropyltrimethoxysilane (KBM-5103, Shin-Etsu Chemical Co., Ltd.) (C-3) N-phenyl-3-aminopropyltrimethoxysilane (KBM-573, Shin-Etsu Chemical Co., Ltd.) (C-4) n-Hexyltrimethoxysilane (KBM-3063, manufactured by Shin-Etsu Chemical Co., Ltd., for comparison)

[0046] (D) Organic solvent (D-1) Toluene

[0047] Preparation of the Slurry Composition Various slurry compositions were produced in the amounts (parts by mass) shown in Table 1. The cyclic imide compound (A), silica fine particles and / or alumina fine particles (B), and the silane coupling agent (C) (except for Comparative Examples 1 and 2) were added to the organic solvent (D) and premixed with a stirrer to prepare a crude slurry solution. This crude slurry solution was dispersed with a disperser to obtain a slurry composition in which the filler was uniformly dispersed. The following properties of the slurry composition were measured. The results are shown in Table 1.

[0048] Agglutination test The obtained slurry composition was applied to a 30 μm thick, A4 size coating on a 38 μm thick polyethylene terephthalate (PET) film (G2-38, manufactured by Teijin) as a supporting substrate using a Baker-type applicator, and dried at 120° C. After drying, the coating in which no aggregates were visually observed was marked with an ◯, and the coating in which at least one aggregate was observed was marked with an ×.

[0049] Viscosity measurement, thixometry ratio calculation The viscosity of the obtained slurry composition was measured at 25° C., 5 rpm and 50 rpm using a cone-plate type rotational viscometer described in JIS K 7117-2: 1999. The thixotropy ratio was calculated from the measured values ​​according to the following formula. Thixotropy ratio = (viscosity measured at 5 rpm [Pa s]) / (viscosity measured at 50 rpm [Pa s])

[0050] Making of molded products Next, 2 parts by mass of dicumyl peroxide (product name: Percumyl D, manufactured by NOF Corp.) was added to 100 parts by mass of each of the slurry compositions of Examples 1, 2, 3 and 5 and Comparative Examples 1 and 3, and dissolved. Then, each slurry composition was poured into a Teflon-coated mold for preparing test pieces, and the organic solvent was evaporated at 100°C for 1 hour, and then the composition was cured at 175°C for 2 hours to obtain a 1A-type test piece described in JIS K 7161-2:2014. The following characteristics were measured using this test piece. The results are shown in Table 2.

[0051] Measurement of tensile strength, tensile stress, and tensile strain The tensile strength, tensile stress, and tensile strain were measured at 25°C according to the method of JIS K 7161-1:2014.

[0052] Measurement of dielectric constant and dielectric tangent In the same manner as in the preparation of the above-mentioned molded product, each slurry composition was cured to obtain a film having a thickness of 200 μm. Then, a network analyzer (E5063-2D5 manufactured by Keysight Corporation) was connected to a strip line (manufactured by Keycom Corporation) to measure the relative dielectric constant and dielectric loss tangent of the film at a frequency of 10 GHz.

[0053] [Table 1]

[0054] [Table 2]

[0055] From the above results, it is clear that the slurry composition of the present invention has low thixotropy and excellent handling properties. In addition, the film formed from the slurry composition has excellent mechanical properties, low dielectric constant and dielectric loss tangent, and the molded product formed from the slurry composition is suitable for use as a material for high-frequency devices.

Claims

1. A slurry composition comprising the following components (A) to (D): a thixotropic ratio calculated from viscosity measured at 25°C / 5 rpm and 50 rpm using a cone-plate type rotational viscometer (E-type viscometer) according to JIS K 7117-2:1999 according to the formula thixotropic ratio = (viscosity measured value at 5 rpm [Pa s]) / (viscosity measured value at 50 rpm [Pa s]) of 3.0 or less: (A) A cyclic imide compound containing at least one dimer acid skeleton, at least one linear alkylene group having 6 or more carbon atoms, and at least two cyclic imide groups in the molecule, and represented by the following formula (1): 15 to 85% by mass in the slurry composition 【Chemistry 1】 (In formula (1), A independently represents a compound represented by the following structural formula, which contains an aromatic ring or an aliphatic ring.) 【Chemistry 2】 (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).) and B is a tetravalent organic group represented by the following structural formula: 【Chemistry 3】 (The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (1).) and Q is independently a linear alkylene group having 6 to 20 carbon atoms. R is independently a linear or branched alkyl group having 6 to 12 carbon atoms. n is a number from 1 to 10. m is a number from 0 to 10. (B) Spherical silica fine particles and / or alumina fine particles having an average particle size of 0.05 to 20 μm as measured by a laser diffraction method: an amount of 35% by mass or more and 90% by mass or less of the entire slurry composition (C) a silane coupling agent having a (meth)acrylic group and / or an amino group, which is capable of reacting with the components (A) and (B). : 0.3 to 6.0 mass% based on component (A) (D) Aromatic Hydrocarbon Organic Solvents 20 to 200 parts by mass per 100 parts by mass of the total of the (A) component and the (B) component

2. A cured product of the slurry composition according to claim 1.

3. The cured product according to claim 2, which is a substrate.

4. The cured product according to claim 2, which is a film.

5. The cured product according to claim 2, which is a prepreg.

Citation Information

Patent Citations

  • Polyphenylene ether resin composition, prepreg, metal-clad laminate, and printed wiring board

    JP2010059363A

  • Polyphenylene ether resin composition, prepreg, metal-clad laminate and printed-wiring board

    JP2010275342A

  • Resin composition, prepreg, laminate, resin sheet, printed wiring board and semiconductor device

    JP2012255059A

  • Adhesive for electronic component and manufacturing method of semiconductor chip package

    JP2013110422A

  • Resin film, resin film with support, prepreg, metal-clad laminated sheet for high multilayer, and high multilayer printed wiring board

    JP2016131243A